An Examples of the Science of Semantics in the Explanations of Al-Babarti and Tabrizi on the Book of Al-Talkhis of al-Qazwini: A Balancing study - Jawad, Karrar; Mahmud , Imad (Al-Adab Journal, 2025)
Semantics was and still is a very important science in modern and ancient linguistic studies. It is not hidden from anyone who investigates the origins of semantics the extent of the strenuous efforts of the early scholars in its path. Rhetoricians have been keen to establish rhetorical rules and search for evidence for them from the Holy Qur’an and from the poetry and prose of the Arabs, until those efforts led to the establishment of a complete science with its well-known topics, which is known as “semantics.” Al-Qazwini’s book “Al-Talkhees” is considered one of the most important books written on Arabic rhetoric, as commentaries on it followed one after the other. I have chosen two of these commentaries to study in this research. This research aims to identify the most important phenomena of rhetorical development in terms of addressing, presenting, and analyzing evidence, as produced by Al-Babarti (786 AH) and Al-Tabrizi (855 AH) in their commentaries, especially after rhetoric had made great strides in development at the hands of many scholars, until it reached what it is in the eighth century AH. I adopted the method of comparison in the research, so after describing and analyzing some of the texts included in the two commentaries, I proceeded to make a comparison between them, to reach the similarities and differences between the two commentaries. The researcher finds that the two commentaries are of great importance in the field of rhetorical research; because they sought to clarify many of the evidences of their predecessors, in addition to their use of evidence that no one else had dealt with, and this will become clear to anyone who reads the research.